Introducing cultural anthropology - Roberta Edwards Lenkeit (McGraw-Hill, 2009)
Introducing Cultural Anthropology, a short yet comprehensive anchor text, is an approachable, full-color introduction to cultural anthropology. This edition continues to provide students with the opportunity to explore anthropology's relevance to their own lives. Unique opening vignettes draw students into each chapter while the rich visual program allows professors to use a brief text without sacrificing visual appeal. "Try This" exercises encourage students to think critically and apply anthropological concepts, perspectives and methods, and the "Anthropology Around Us" boxes focus on the application of anthropological concepts featured in each chapter